Enhancement of post-activation performance enhancement by blood flow restriction following specific on-ice exercise program in ice hockey players - Gabrys, Tomasz; Chruscinski, Radoslaw; Szmatlan-Gabrys, Urszula; Garnys, Michal; Bichowska-Paweska, Marta; Cepicka, Ladislav (Frontiers in Sports and Active Living, 2025)
IntroductionDue to the requirements for research on motor skills in elite hockey players, an attempt was made to assess the skills following the application of PAPE and BFR-enhanced PAPE to enhance lower limb power.MethodsAn on-ice exercise program was used to determine PAPE factors that included three sets of 3 repetitions of specific on-ice effort, 15 s of work, 15 s of rest, separated by 90 s of free skating. The evaluation of the effectiveness of the PAPE program was measured at the 3rd, 6th, 9th, 12th, and 15th minutes after its application. The flight time during the CMJ and SJ jump was recorded with the OptoJump system, and the jump height (JH) and peak power (PP) were determined. The study involved 20 professional male hockey players aged 17 ± 1 years with 11 ± 2 years of training experience.ResultsNo differences between JH and PP values in CMJ and SJ before and after PAPE and PAPE with BFR intervention were statistically significant. The BFR application during specific effort showed a statistically significant p ≤ 0.001 increase in work time.DiscussionSignificant individual differences in the magnitude of the PAPE and BFR effect between the subjects were also found. The individualization of exercise stimuli should consider the individual athlete's profile in terms of susceptibility to the PAPE and BFR program, considering the amount of fatigue it may cause.